A brief comment on the numerical results in 'Electrostatic potential of a uniformly charged triangle in barycentric coordinates'. (26th August 2021) - Ferreira, Diogo R
Abstract: In a recent paper (2021 Eur. J. Phys. 42 045205), Kim et al carry out an analytical effort to arrive at an expression for the electrostatic potential due to a uniformly charged triangle. This appears to have been attempted by other authors before, with similar, but not exactly equal, numerical results. In addition, the paper leaves some doubts with regard to the comparison of the analytical expressions by different authors and the agreement of their numerical results. What, then, is the true electrostatic potential of a uniformly charged triangle? This comment does not answer this question but provides an independent effort to confirm the numerical results.